2008
DOI: 10.1002/nag.764
|View full text |Cite
|
Sign up to set email alerts
|

Modeling crack propagation path of anisotropic rocks using boundary element method

Abstract: SUMMARYIn a cracked material, the stress intensity factors (SIFs) at the crack tips, which govern the crack propagation and are associated with the strength of the material, are strongly affected by the crack inclination angle and the orientation with respect to the principal direction of anisotropy. In this paper, a formulation of the boundary element method (BEM), based on the relative displacements of the crack tip, is used to determine the mixed-mode SIFs of isotropic and anisotropic rocks. Numerical examp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Aliabadi and Sollero (1998) proposed a 2D anisotropic material model suitable for implementation in a Boundary Element Method (BEM) code. The model was used to simulate crack propagation in UD fibre-reinforced composites (Aliabadi and Sollero 1998) and in rocks (Chen et al 1998;Ke et al 2009). Motamedi and Mohammadi (2010) further developed the extended FEM (X-FEM) to simulate crack propagation in 2D…”
Section: Introductionmentioning
confidence: 99%
“…Aliabadi and Sollero (1998) proposed a 2D anisotropic material model suitable for implementation in a Boundary Element Method (BEM) code. The model was used to simulate crack propagation in UD fibre-reinforced composites (Aliabadi and Sollero 1998) and in rocks (Chen et al 1998;Ke et al 2009). Motamedi and Mohammadi (2010) further developed the extended FEM (X-FEM) to simulate crack propagation in 2D…”
Section: Introductionmentioning
confidence: 99%
“…In Ke et al [ 133 ], the authors have suggested a methodology to obtain the fracture toughness of anisotropic rocks through experimental measurements of the elastic parameters and further comparison with a BEM code. In another work, Ke et al [ 132 ] have proposed a crack propagation model for transversely isotropic rocks. Let us remark that all the previously mentioned works have used the Lekhnitskii formalism [ 145 ] in order to model the anisotropy of the material.…”
Section: Discrete Numerical Methodsmentioning
confidence: 99%
“…In a series of studies conducted by Chen et al [20,22,27], the crack initiation angle in homogeneous anisotropic CBD specimens made of marble and shale were investigated both experimentally and numerically with the Boundary Element Method (BEM). Chen et al [90,91] proposed the indirect (Brazilian) tensile strength to determine mechanical properties of rock specimens.…”
Section: Mixed-mode Fracture In Anisotropic Homogeneous Cbd Specimensmentioning
confidence: 99%
“…The effect of material anisotropy on the mode I stress intensity factors (SIFs) by a 3D Finite Element Method was also investigated and reported by Hirose et al [15]. Recently many attempts have been conducted to characterize the effects of geometric parameters (crack length, crack inclination angle, geometric shape of specimen) and mechanical properties (Poisson's ratio, degree of material anisotropy and anisotropic orientation) in homogeneous anisotropic materials [9,12,14,[16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%